Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/mnras/stv2978
|View full text |Cite
|
Sign up to set email alerts
|

Stellar population constraints on the ages of galactic bars

Abstract: We present a study of the stellar populations within the central regions of four nearby barred galaxies, and use a novel technique to constrain the duration of bar activity. We focus on the star formation 'desert', a region within each of these galaxies where star formation appears to have been suppressed by the bar. New Hβ spectroscopic data are presented, and used to produce spectroscopic line indices which are compared with theoretical predictions from population synthesis models for simple stellar populati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
68
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 46 publications
5
68
0
Order By: Relevance
“…The formation and dynamics of bars is potentially an important mechanism for regulating the evolution of the star-formation rate in disk galaxies. While studies have highlighted a possible link between the star formation and the existence of bars in disk galaxies (see e.g., Laurikainen et al 2004a;Jogee et al 2005;Masters et al 2010;Ellison et al 2011), by studying the central regions of four strongly barred galaxies, James & Percival (2016) showed that the recent star formation appears to have been suppressed by the bars. By reconstructing the star-formation history of main-sequence galaxies from z = 3 to the present epoch, Gavazzi et al (2015) found that star-forming galaxies quenched above a mass threshold which increases with increasing redshift.…”
Section: Introductionmentioning
confidence: 99%
“…The formation and dynamics of bars is potentially an important mechanism for regulating the evolution of the star-formation rate in disk galaxies. While studies have highlighted a possible link between the star formation and the existence of bars in disk galaxies (see e.g., Laurikainen et al 2004a;Jogee et al 2005;Masters et al 2010;Ellison et al 2011), by studying the central regions of four strongly barred galaxies, James & Percival (2016) showed that the recent star formation appears to have been suppressed by the bars. By reconstructing the star-formation history of main-sequence galaxies from z = 3 to the present epoch, Gavazzi et al (2015) found that star-forming galaxies quenched above a mass threshold which increases with increasing redshift.…”
Section: Introductionmentioning
confidence: 99%
“…These regions also display a deficit in surface stellar density (Gadotti & de Souza 2003;Gadotti 2008;Kim et al 2016). James & Percival (2016, 2018 assumed a truncated star formation model and found that SFD regions can be very old. If the truncation of star formation is caused by the bar, this feature can be used to determine the epoch of bar formation.…”
Section: Introductionmentioning
confidence: 99%
“…Urquhart et al 2018) and therefore star formation is likely to be intermittent in time as well. Moreover, the effect of the Galactic bar on star formation within 3-4 kpc of the Galactic Centre is poorly understood, but the presence of a bar may suppress star formation (James & Percival 2016) and (as simulations have shown) disrupt the dynamics throughout the disc (e.g. Dobbs & Pringle 2010).…”
Section: Introductionmentioning
confidence: 99%